2022
DOI: 10.1063/5.0093978
|View full text |Cite
|
Sign up to set email alerts
|

Shock wave and bubble pulsation characteristics in a field generated by single underwater detonation

Abstract: To promote the development and application of underwater detonation propulsion technology, we built a single underwater detonation experimental system and established the corresponding axisymmetric five-equation model to study the characteristics of the flow field generated by a single underwater detonation. The shock wave formed by the degeneration of the detonation wave in the detonation tube interacted with the water-gas interface. Moreover, the jetting of detonated gas was blocked by water, which sharply i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Thereafter, a larger bubble with a diameter of d ≈3.5 mm exploded with a time delay (frame 6), despite it being subjected to shock compression earlier, being somewhat upstream with respect to the two bubbles that exploded earlier. Furthermore, this bubble expanded (frame 7), shrank again (frame 8) and expanded again (frames 9-11), taking the shape of a parachute (frames 12-14), and then broke up into small fragments (frames [15][16][17][18][19][20]. The processing of video records made it possible to gain information on the shockinduced motion of individual bubbles behind the traveling SW.…”
Section: Single Shock Wave Propagation In Bubbly Watermentioning
confidence: 99%
See 1 more Smart Citation
“…Thereafter, a larger bubble with a diameter of d ≈3.5 mm exploded with a time delay (frame 6), despite it being subjected to shock compression earlier, being somewhat upstream with respect to the two bubbles that exploded earlier. Furthermore, this bubble expanded (frame 7), shrank again (frame 8) and expanded again (frames 9-11), taking the shape of a parachute (frames 12-14), and then broke up into small fragments (frames [15][16][17][18][19][20]. The processing of video records made it possible to gain information on the shockinduced motion of individual bubbles behind the traveling SW.…”
Section: Single Shock Wave Propagation In Bubbly Watermentioning
confidence: 99%
“…The authors of [16] used high-speed photography and image post-processing to register time-resolved structural changes in a submerged gaseous jet emanating from a Laval nozzle. In [17], the results of experimental study on gas jetting by an underwater detonation tube were reported, and the mechanism of shock wave propagation and bubble deformation was discussed. The effect of the nozzle attached to a detonation tube on the underwater SW and gas detonation bubble was investigated in [18].…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al [27] used high-speed photography and image post-processing to register time-resolved structural changes in a submerged gaseous jet emanating from a Laval nozzle. Wang et al [28] reported the results of numerical simulation and experimental study on gas jetting by an underwater DT and discussed the mechanism of shock wave propagation and bubble deformation. Wang et al [29] investigated both computationally and experimentally the effect of the nozzle attached to a DT on the underwater shock wave and gas detonation bubble.…”
Section: Introductionmentioning
confidence: 99%